Parental eating disorders: A systematic review of parenting attitudes, behaviours, and parent-child interactions. (August 2021) - Chapman, Laura; Cartwright-Hatton, Sam; Thomson, Abigail; Lester, Kathryn J.
Abstract: A substantial proportion of adults with eating disorders are parents. Studies suggest these parents may experience a range of parenting challenges, and their children may be at an increased risk for the development of eating disorders themselves. With parenting practices being one potential environmental mechanism for the intergenerational transmission of eating disorders, we systematically searched Scopus, Web of Science, PubMed, MEDLINE, PsychINFO, and PsychArticles for controlled studies in which parenting attitudes, behaviours, and parent-child interactions were examined for parents with and without probable eating disorders. 26, 512 abstracts were screened, and 167 full-text manuscripts were retrieved, with 33 studies meeting the review inclusion criteria. Studies suggest that parents with eating disorders experience higher levels of parenting stress than control parents, and may on average be more intrusive, less sensitive, and provide less structuring/facilitation in non-feeding interactions with their children. These parents also appear, on average, to experience increased concern about their children's weight, and parent-child mealtime interactions may be problematic and characterised by high levels of conflict. Suggestions for future research are made with a view to enhancing understandings of the intergenerational transmission of eating disorders, which may lead to the identification of intervention targets for parents with eating disorders and their children. Highlights: Parental eating disorders (ED) may disrupt general parenting. ED may influence parenting practices such as feeding behaviours. Parental eating disorders may affect parent-child interactions. Parenting factors may contribute to the intergenerational transmission of ED.